TINJAUAN HUKUM ISLAM TERHADAP PELAKSANAAN GADAI POHON DURIAN DI DESA BLIMBING KECAMATAN DOLOPO KABUPATEN MADIUN - Choirul Huda, Fran Aldino (Ngabari: Jurnal Studi Islam dan Sosial, 2020)
This study aims to determine the implementation of durian tree pawning in Blimbing Village, Dolopo District, Madiun Regency, and to determine the review of Islamic law on the implementation of durian tree pawning in the area. A qualitative descriptive approach was used in this study. This research resulted in findings, 1) the implementation of durian tree pawning in Blimbing village begins with the arrival of the durian tree owner to the money owner's place to borrow money, the money owner checks the quality of the durian tree which will be used as a guarantee, if there is an agreement they sign the pawning agreement, by bringing in a witness. 2) There are deficiencies in the practice of pawning durian trees in Blimbing Village Dolopo Madiun because Murtahin takes all of the durian tree harvests even though the value exceeds the amount of money lent, maintenance costs for the durian tree are borne by Rahin. But every year there are still durian farmers who mortgage their durian trees, because of the advantages they feel the process is easy, fast, and practical. 3) There is an element of usury in the practice of pawning durian trees in Blimbing Village Dolopo Madiun.